ANALYSIS OF INTERACTION OF QUALITY POISONING AND QUANTITY INDICES ON THE BACKGROUND OF ETHANOL ALCOHOLIC LIVER DISEASE - E. N. Travenko; V. A. Porodenko (Кубанский научный медицинский вестник, 2016)
We studied the correlation between quantitative and qualitative-governmental indicators for poisoning with ethanol on a background of alcoholic liver disease (110 cases). The positive and negative relation between the varying degree of alcohol content in the departments of venous and alkogolokislyayuschih activity of enzyme systems (AOFS) level alkogolemii and necro-inflammatory processes in the liver, morphological manifestations of poisoning with ethanol and the state AOFS. Revealed high negative correlation between the diameter of the portal vein, the number of blood vessels of medium caliber and the development of fibrosis.